Evaluasi Overhaul terhadap Efisiensi Boiler Unit 3 PLTU Lontar - Eri Prabowo; Trassanda Scudetto Widestomo Putra; Ajibrila Nabawi (JTM : JURNAL TEKNIK MESIN, 2026)
The boiler is the main component of a steam power plant because it converts feedwater into high-temperature and high-pressure steam for turbine operation. Boiler efficiency is affected by combustion quality, coal characteristics, air supply, heat-transfer cleanliness, and the condition of auxiliary equipment. This study evaluates the effect of overhaul on the efficiency of Boiler Unit 3 at UJP PLTU Banten 3 Lontar. The calculation uses performance-test data before and after overhaul at a 294 MW load. Two methods are applied: the direct or input-output method and the indirect or heat-loss method based on ASME PTC 4. The direct-method efficiency increased from 79.51% before overhaul to 79.68% after overhaul, equivalent to a 0.17 percentage-point improvement. The indirect-method efficiency increased from 81.85% to 82.61%, equivalent to a 0.76 percentage-point improvement. The reduction in dry flue-gas loss, hydrogen-moisture loss, coal-moisture loss, and air-moisture loss indicates that overhaul improves boiler heat utilization, especially through tube cleaning, air-preheater cleaning, and restoration of combustion-supporting equipment. The results confirm that scheduled overhaul can improve boiler performance and should be maintained as part of plant reliability management